O negro em Viva o povo brasileiro: representações na ficção ubaldiana - Silva, Thaíse Araújo da (2015)
This dissertation analyses the image of blacks in Brazil through the literary representation from the novel Viva o povo brasileiro(1984), by João Ubaldo Ribeiro. The author’s narrative presents the root formation of the Brazilian people, recounting and establishing a critical on country history. From this perspective, Viva o povo Brasileiro acts as a form of reflection by showing scenes which reveals the suffering of a people throughout history of brazil., using the ficcional text as a funding vehicle of images from brazilian society in the specified epoch in pages from the novel. So, the research highlights the black characters from the narrative, with the intention of enhancing the people which were essential to Brazil’s cultural, ethnics and economical formation, insisting on a intertextuality relationship with history of Brazil, by mentioning the representation of the discursive formation, power relationship and the domination elements used against the blacks. In view of this, it’s analysed the ficcional and historical landmarks which features the blacks on the novel through the verisimilitude between episodes from the novel and the historical facts of the country, articulating the ficcional elements of the book to racists discourses, intending to highlight the social system of domination, based ethnic or "racially" and its consequent inequality. Thus, from suck analyses, it’s concluded that João Ubaldo Ribeiro’s narrative, is not a historical novel, but rather a literary narrative that represents a meaninful quantity of the historical contexts of the country.